PERILAKU PERAWATAN KEHAMILAN DALAM PERSPEKTIF BUDAYA JAWA DI DESA KALIORI KECAMATAN KALIBAGOR - Murniasih, Ni Putu; Masfiah, Siti; Hariyadi, Bambang (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2016)
One of the causes of the high maternal mortality rate in Indonesia is the lack of knowledge about prenatal care and the cultural influences that have been passed down from generation to generation ancestors. This study aimed to determine the prenatal care in Javanese culture perspective Kaliori Village, District of Kalibagor. This study used a qualitative approach postpartum mothers as key informan and leaders and midwives as supporters informants are community. Data analysis was performed by content analysis. The results showed pregnant women performed rituals that were ngupati and mitoni, food taboos and believed in pregnancy myths. Pregnant women who live with their parents or they did parent in-laws have the intention to do that behavioral, but pregnant women who live alone do not have the intention to performed that. Pregnant women felt happy to get any attention from most influence person for them.  Selecting the information obtained from of friends, internet, family and midwife was as control behavior. Midwife advice that pregnant women should not refrain from some food because it can cause anemia and low birth weight infants. Study recommend  midwives and community leaders working together to provide socialization in prenatal care, especially related to food taboos and myths about pregnancy.